A new quinoxaline and isoindigo based polymer as donor material for solar cells: Role of ecofriendly processing solvents on the device efficiency and stability. Issue 2 (21st September 2016) - Seri, Mirko; Gedefaw, Desta; Prosa, Mario; Tessarolo, Marta; Bolognesi, Margherita; Muccini, Michele; Andersson, Mats R.
ABSTRACT: A new semiconducting polymer based on two different electron deficient (quinoxaline and isoindigo) and electron rich (benzodithiophene) moieties is synthesized, characterized and used as donor material for photovoltaic devices. Blade‐coated bulk heterojunction solar cells are fabricated in air by using chlorinated ( o ‐dichlorobenzene) and nonchlorinated ( o ‐xylene) solvents for the deposition of the active layer. The use of o ‐xylene allows a ∼10% improvement of the device efficiency in comparison to the analogous system processed from o ‐dichlorobenzene. In addition, the evolution of the photovoltaic parameters of the resulting devices during thermal stress is monitored and compared, demonstrating a nearly identical resistance against temperature. The reported results not only highlight the promising properties of the new polymer in terms of environmental stability and compatibility with nonhalogenated solvents, but also show an easy and ecofriendly way to further improve the device performance without altering the corresponding thermal stability. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 234–242 Abstract : A novel semiconducting polymer based on the combinations of three different building blocks (quinoxaline, isoindigo, and benzodithiophene) has been prepared and characterized. By using the polymer as donor material, blade‐coated bulk heterojunction solar cells (processed in air) from chlorinated and nonchlorinated solvents are fabricated and then compared to evaluate the impact of the processing solvent on the device efficiency and stability.